A preparation process and application of high-performance polylactic acid meltblown cloth
By mixing polylactic acid with other compounds and additives, spraying and electrostatic treatment, high-performance polylactic acid meltblown cloth is prepared, which solves the shortcomings of the existing polypropylene meltblown cloth in terms of filtration and biodegradability, and achieves better heat resistance and hydrophobic oil absorption, and is suitable for mass production and mask production.
Patent Information
- Application Number
- CN202210234069.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-03-10
AI Technical Summary
The existing polypropylene meltblown cloth has shortcomings in terms of filtration and biodegradability, which have poor filtration and poor biodegradability.
Polylactic acid is used as the main raw material, and high-performance polylactic acid meltblown cloth is prepared by mixing distilled water, polylactic acid, carboxylic compounds, enhancers, compatibilizers and surface regulators, and adding electret masterbatches and anti-hydrolysis masterbatches.
It improves the heat resistance and hydrophobic oil absorption of polylactic acid meltblown cloth, meets the mass production needs of high-performance meltblown cloth, and is especially suitable for mass production of masks.
Smart Images

Figure BDA0003541115530000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of meltblown cloth, with an IPC classification number of D04H 1 / 4382, and in particular to a preparation process and application of a high-performance polylactic acid meltblown cloth. Background Art
[0002] Meltblown cloth is mainly made of polypropylene as the main raw material. Its fiber diameter is small, reaching the micron level, with many gaps, fluffy structure, and good anti-wrinkle performance. The ultrafine fiber with unique capillary structure can increase the surface area of the unit fiber, making the meltblown cloth have better filtering and shielding properties. It is often used to make mask materials, isolation materials, oil-absorbing materials and wiping cloths, etc.
[0003] The meltblown cloth filter material is composed of randomly distributed and bonded polypropylene ultrafine fibers. The fiber fineness of the material can reach 0.5-1.0μm. The random distribution of the fibers allows for better adhesion between the fibers, thereby increasing the specific surface area and porosity of the meltblown gas filtration. After high-pressure electret filtration, the product has the characteristics of low resistance, high efficiency, and high dust holding capacity.
[0004] Patent CN202010962912.2 discloses a method for preparing an electret meltblown cloth material based on zeolite and polypropylene. The raw materials for preparation include polypropylene, zeolite, and electret masterbatch zeolite. A meltblown cloth material is prepared by stirring and mixing the above raw materials and then melt-treating them. The meltblown cloth material has the advantages of simple antistatic preparation process, but its filterability is poor.
[0005] Patent CN202110105047.4 discloses a method for preparing modified polypropylene meltblown cloth treated with electret treatment. The polypropylene is modified by mixing it with nano-SiO2 and then subjected to a meltblown spinning preparation process. The prepared meltblown cloth has high electret charge stability and can be used for durable and efficient filter materials, but its biodegradability is poor. Summary of the invention
[0006] The first aspect of the present invention provides a preparation process of a high-performance polylactic acid meltblown cloth, the preparation steps of which include:
[0007] (1) adding distilled water to a reaction kettle, raising the temperature, then adding polylactic acid, a carboxyl compound, a reinforcing agent, a compatibilizer, and a surface conditioning agent, mixing and stirring to obtain a mixture a, sampling the mixture a to detect the melt index during the stirring, stopping the reaction when a specific melt index is reached, and discharging the mixture to obtain a mixture b;
[0008] (2) placing the mixture b in a container, adding the electret masterbatch and the anti-hydrolysis masterbatch thereto, stirring and mixing, to obtain a mixture c;
[0009] (3) The spraying temperature is adjusted, the mixture c is sprayed, and then an electrostatic treatment is performed to prepare a high-performance polylactic acid melt-blown cloth.
[0010] Preferably, the heating temperature is 65-85°C;
[0011] Preferably, the mixing and stirring time is 5-20h;
[0012] Preferably, the specific melt index is 150-800 g / 10 min, 190° C., 2.16 kg;
[0013] Preferably, the spraying temperature is 160-230°C;
[0014] Preferably, the carboxyl compound is a combination of one or more of tartaric acid, sodium benzoate, malic acid, adipic acid, citric acid, glycine, succinic acid, maleic acid, and acetic acid;
[0015] Further preferably, the carboxyl compound is a compound of sodium benzoate and adipic acid, and the mass ratio of sodium benzoate to adipic acid is 1:0.4-0.8;
[0016] Preferably, the reinforcing agent is a combination of one or more of erucamide, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyhydroxybutyrate, acrylic acid-hydroxypropyl acrylate copolymer, polybutylene terephthalate-adipate, polymer polyol, and polycaprolactone;
[0017] Further preferably, the reinforcing agent is a compound of ethylene-vinyl acetate copolymer and polybutylene terephthalate-adipate, and the mass ratio of ethylene-vinyl acetate copolymer to polybutylene terephthalate-adipate is 0.5-1.1:0.8-1.4;
[0018] Preferably, the compatibilizer is maleic anhydride grafted polyolefin;
[0019] Preferably, the polyolefin is one or a combination of polyethylene, polypropylene, ethylene-vinyl acetate copolymer, poly-1-butene, polypropylene, poly-4-methyl-1-pentene, cycloolefin copolymer, ethylene-1-octene copolymer, ethylene propylene diene monomer rubber, and hydrogenated styrene-butadiene block copolymer;
[0020] Further preferably, the compatibilizer is a compound of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, and the mass ratio of maleic anhydride grafted polypropylene to maleic anhydride grafted polyethylene is 0.4-0.7:0.8-1.3;
[0021] Preferably, the surface conditioner is one or a combination of polystyrene methyl methacrylate, poly(methyl methacrylate-co-methacrylic acid), poly(ethylene-co-glycidyl methacrylate), poly(ethylene-co-acrylic acid), poly(styrene)-block-poly(acrylic acid);
[0022] Further preferably, the surface regulator is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), and the mass ratio of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid) is 0.5-1.2:0.7-0.9:0.3-0.5.
[0023] Preferably, the filter material of the electret masterbatch is polypropylene;
[0024] Preferably, the melt flow rate of the electret masterbatch is 1000-2000 g / 10 min, and the test conditions are 230° C., 2.16 kg;
[0025] Preferably, the melt flow rate of the electret masterbatch is 1500 g / 10 min, and the test conditions are 230° C., 2.16 kg; (PolyOne, brand: n95);
[0026] Preferably, the preparation method of the hydrolysis-resistant masterbatch is: PET, polycarbodiimide and calcium oxide are dried for 2-6 hours, stirred in a high-speed mixer for 10-15 minutes, and cooled and granulated by a double-screw melt extruder at 200-280°C and 300-500rpm to obtain;
[0027] The second aspect of the present invention provides an application of a preparation process of a high-performance polylactic acid meltblown fabric, which is used in the production of masks.
[0028] Beneficial effects:
[0029] (1) The present invention provides a preparation process for high-performance polylactic acid meltblown cloth by mixing distilled water, polylactic acid, a carboxyl compound, a reinforcing agent, a compatibilizer, a surface regulator, a polarizing masterbatch, and an anti-hydrolysis masterbatch. The prepared meltblown cloth has good heat resistance and hydrophobic oil absorption, and can meet the needs of mass production of high-performance meltblown cloth.
[0030] (2) The addition of a surface regulator in the present invention can improve the heat resistance and oil absorption of the obtained meltblown fabric product, especially when the surface regulator is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), and the mass ratio of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid) is 0.5-1.2:0.7-0.9:0.3-0.5. The reason may be that the surface regulator contains a relatively long alkyl molecular chain, and contains a branched chain and a conjugated structure, and has a synergistic effect with the reinforcing agent and the compatibilizer. When a specific heating temperature and mixing and stirring time are set, and polylactic acid is degraded to a specific melt index, the carboxyl compound can be promoted to degrade the molecular chain of polylactic acid, thereby improving the poor heat resistance and oil absorption of the polylactic acid meltblown fabric product.
[0031] (3) Polylactic acid has good biocompatibility and good biodegradability, but due to the influence of its own molecular chain structure, the prepared meltblown cloth has problems such as poor heat resistance and oil absorption. The present invention mixes distilled water, polylactic acid, carboxyl compounds, enhancers, compatibilizers, and surface regulators, and adds electret masterbatch and anti-hydrolysis masterbatch to mix them, and then sprays the cloth and performs electrostatic treatment. By setting a specific heating temperature and mixing time, and degrading polylactic acid to a specific melt index, the heat resistance and poor oil absorption of the polylactic acid meltblown cloth product can be improved. A preparation process for high-performance polylactic acid meltblown cloth is provided, and a meltblown cloth is prepared. The meltblown cloth has good heat resistance and hydrophobic oil absorption, can meet the mass production of high-performance meltblown cloth, and is particularly suitable for mass production of masks. DETAILED DESCRIPTION
[0032] Example 1
[0033] Example 1 provides a preparation process for a high-performance polylactic acid meltblown cloth, the preparation steps of which include:
[0034] (1) adding distilled water to a reaction kettle, raising the temperature, then adding polylactic acid, a carboxyl compound, a reinforcing agent, a compatibilizer, and a surface conditioning agent, mixing and stirring to obtain a mixture a, sampling the mixture a to detect the melt index during the stirring, stopping the reaction when a specific melt index is reached, and discharging the mixture to obtain a mixture b;
[0035] (2) placing the mixture b in a container, adding the electret masterbatch and the anti-hydrolysis masterbatch thereto, stirring and mixing, to obtain a mixture c;
[0036] (3) adjusting the spraying temperature, spraying the mixture c, and then performing an electrostatic treatment to prepare a high-performance polylactic acid melt-blown cloth;
[0037] The weight portion of distilled water is 40 parts;
[0038] The polylactic acid has a weight of 30 parts and is purchased from Total Corbijn, model number L130;
[0039] The heating temperature is 65°C;
[0040] The mixing and stirring time is 5h;
[0041] The specific melt index is 150 g / 10 min, 190° C., 2.16 kg;
[0042] The spraying temperature is 160°C;
[0043] The carboxyl compound is a compound of sodium benzoate and adipic acid, with a weight portion of 0.1 parts, a mass ratio of sodium benzoate to adipic acid of 1:0.4, sodium benzoate CAS No. 532-32-1, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., adipic acid CAS No. 124-04-9, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0044] The reinforcing agent is a compound of ethylene-vinyl acetate copolymer and polybutylene terephthalate-adipate, with a weight portion of 5 parts, a mass ratio of ethylene-vinyl acetate copolymer to polybutylene terephthalate-adipate of 0.5:0.8, CAS number of ethylene-vinyl acetate copolymer is 24937-78-8, purchased from Shanghai Yien Chemical Technology Co., Ltd., and CAS number of polybutylene terephthalate-adipate is 55231-08-8, purchased from Shanghai McLean Biochemical Technology Co., Ltd.;
[0045] The compatibilizer is a compound of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, with a weight portion of 0.5 parts, a mass ratio of maleic anhydride grafted polypropylene to maleic anhydride grafted polyethylene of 0.4:0.8, the maleic anhydride grafted polypropylene model is American Dow 105TY, purchased from Shangxi (Shanghai) Chemical Additive Co., Ltd., and the maleic anhydride grafted polyethylene CAS number is 9006-26-2, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0046] The surface conditioner is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), with a weight portion of 0.5 parts, a mass ratio of poly(ethylene-co-glycidyl methacrylate) to poly(styrene)-block-poly(acrylic acid) of 0.5:0.7:0.3, polystyrene methyl methacrylate CAS No. 25034-86-0, purchased from West Asia Chemical Technology (Shandong) Co., Ltd., poly(ethylene-co-glycidyl methacrylate) CAS No. 26061-90-5, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., and poly(styrene)-block-poly(acrylic acid) model No. 747009-500MG, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0047] The filter material of the electret masterbatch is polypropylene;
[0048] The melt flow rate of the electret masterbatch is 1500g / 10min, the test conditions are 230°C, 2.16kg, the brand of the electret masterbatch is PolyOne, the grade is n95;
[0049] The preparation method of the hydrolysis-resistant masterbatch is as follows: PET, polycarbodiimide and calcium oxide are dried for 3 hours, stirred in a high-speed mixer for 11 minutes, and cooled and granulated through a double-screw melt extruder at 220° C. and 350 rpm to obtain the masterbatch;
[0050] The second aspect of the present invention provides an application of a preparation process of a high-performance polylactic acid meltblown fabric, which is used in the production of masks.
[0051] Example 2
[0052] Example 2 provides a preparation process for a high-performance polylactic acid meltblown cloth, the preparation steps of which include:
[0053] (1) adding distilled water to a reaction kettle, raising the temperature, then adding polylactic acid, a carboxyl compound, a reinforcing agent, a compatibilizer, and a surface conditioning agent, mixing and stirring to obtain a mixture, sampling the mixture to detect the melt index during the stirring, and stopping the reaction when a specific melt index is reached, discharging the mixture to obtain a mixture a;
[0054] (2) placing mixture a in a container, adding electret masterbatch and anti-hydrolysis masterbatch thereto, stirring and mixing, to obtain mixture b;
[0055] (3) The spraying temperature is adjusted, the mixture b is sprayed, and then an electrostatic treatment is performed to prepare a high-performance polylactic acid melt-blown cloth.
[0056] The weight portion of distilled water is 70 parts;
[0057] The polylactic acid has a weight of 60 parts and is purchased from Total Corbijn, model L130;
[0058] The heating temperature is 85°C;
[0059] The mixing time is 20h;
[0060] The specific melt index is 800 g / 10 min, 190° C., 2.16 kg;
[0061] The spraying temperature is 230°C;
[0062] The carboxyl compound is a compound of sodium benzoate and adipic acid, with a weight portion of 1 part, a mass ratio of sodium benzoate to adipic acid of 1:0.8, sodium benzoate CAS No. 532-32-1, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., adipic acid CAS No. 124-04-9, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0063] The reinforcing agent is a compound of ethylene-vinyl acetate copolymer and polybutylene terephthalate-adipate, with a weight portion of 10 parts, a mass ratio of ethylene-vinyl acetate copolymer to polybutylene terephthalate-adipate of 1.1:1.4, CAS number of ethylene-vinyl acetate copolymer is 24937-78-8, purchased from Shanghai Yien Chemical Technology Co., Ltd., and CAS number of polybutylene terephthalate-adipate is 55231-08-8, purchased from Shanghai McLean Biochemical Technology Co., Ltd.;
[0064] The compatibilizer is a compound of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, with a weight portion of 1.0 part, a mass ratio of maleic anhydride grafted polypropylene to maleic anhydride grafted polyethylene of 0.7:1.3, the maleic anhydride grafted polypropylene model is American Dow 105TY, purchased from Shangxi (Shanghai) Chemical Additive Co., Ltd., and the maleic anhydride grafted polyethylene CAS number is 9006-26-2, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0065] The surface conditioner is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), with a weight portion of 1.0 part, a mass ratio of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid) of 1.2:0.9:0.5, polystyrene methyl methacrylate CAS No. 25034-86-0, purchased from West Asia Chemical Technology (Shandong) Co., Ltd., poly(ethylene-co-glycidyl methacrylate) CAS No. 26061-90-5, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., and poly(styrene)-block-poly(acrylic acid) model No. 747009-500MG, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0066] The filter material of the electret masterbatch is polypropylene;
[0067] The melt flow rate of the electret masterbatch is 1500g / 10min, the test conditions are 230°C, 2.16kg, the brand of the electret masterbatch is PolyOne, the grade is n95;
[0068] The preparation method of the hydrolysis-resistant masterbatch is as follows: PET, polycarbodiimide and calcium oxide are dried for 6 hours, stirred in a high-speed mixer for 15 minutes, and cooled and granulated through a double-screw melt extruder at 280° C. and 500 rpm to obtain the masterbatch;
[0069] The second aspect of the present invention provides an application of a preparation process of a high-performance polylactic acid meltblown fabric, which is used in the production of masks.
[0070] Example 3
[0071] Example 3 provides a preparation process for a high-performance polylactic acid meltblown cloth, the preparation steps of which include:
[0072] (1) adding distilled water to a reaction kettle, raising the temperature, then adding polylactic acid, a carboxyl compound, a reinforcing agent, a compatibilizer, and a surface conditioning agent, mixing and stirring to obtain a mixture, sampling the mixture to detect the melt index during the stirring, and stopping the reaction when a specific melt index is reached, discharging the mixture to obtain a mixture a;
[0073] (2) placing mixture a in a container, adding electret masterbatch and anti-hydrolysis masterbatch thereto, stirring and mixing, to obtain mixture b;
[0074] (3) The spraying temperature is adjusted, the mixture b is sprayed, and then an electrostatic treatment is performed to prepare a high-performance polylactic acid melt-blown cloth.
[0075] The weight portion of distilled water is 50 parts;
[0076] The weight portion of the polylactic acid is 50 parts, purchased from Total Corbijn, model number is L130;
[0077] The heating temperature is 70°C;
[0078] The mixing time is 15h;
[0079] The specific melt index is 600 g / 10 min, 190° C., 2.16 kg;
[0080] The spraying temperature is 200°C;
[0081] The carboxyl compound is a compound of sodium benzoate and adipic acid, with a weight portion of 0.7 parts, a mass ratio of sodium benzoate to adipic acid of 1:0.6, sodium benzoate CAS No. 532-32-1, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., adipic acid CAS No. 124-04-9, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0082] The reinforcing agent is a compound of ethylene-vinyl acetate copolymer and polybutylene terephthalate-adipate, with a weight portion of 7 parts, a mass ratio of ethylene-vinyl acetate copolymer to polybutylene terephthalate-adipate of 0.8:1.0, CAS number of ethylene-vinyl acetate copolymer is 24937-78-8, purchased from Shanghai Yien Chemical Technology Co., Ltd., and CAS number of polybutylene terephthalate-adipate is 55231-08-8, purchased from Shanghai McLean Biochemical Technology Co., Ltd.;
[0083] The compatibilizer is a compound of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene, with a weight portion of 0.6 parts, a mass ratio of maleic anhydride grafted polypropylene to maleic anhydride grafted polyethylene of 0.6:1.0, the maleic anhydride grafted polypropylene model is American Dow 105TY, purchased from Shangxi (Shanghai) Chemical Additive Co., Ltd., and the maleic anhydride grafted polyethylene CAS number is 9006-26-2, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0084] The surface conditioner is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), with a weight portion of 0.6 parts, a mass ratio of poly(ethylene-co-glycidyl methacrylate) to poly(styrene)-block-poly(acrylic acid) of 1.1:0.8:0.4, polystyrene methyl methacrylate CAS No. 25034-86-0, purchased from West Asia Chemical Technology (Shandong) Co., Ltd., poly(ethylene-co-glycidyl methacrylate) CAS No. 26061-90-5, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., and poly(styrene)-block-poly(acrylic acid) model No. 747009-500MG, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0085] The filter material of the electret masterbatch is polypropylene;
[0086] The melt flow rate of the electret masterbatch is 1500g / 10min, the test conditions are 230°C, 2.16kg, the brand of the electret masterbatch is PolyOne, the grade is n95;
[0087] The preparation method of the hydrolysis-resistant masterbatch is as follows: PET, polycarbodiimide and calcium oxide are dried for 4 hours, stirred in a high-speed mixer for 13 minutes, and cooled and granulated through a double-screw melt extruder at 250° C. and 400 rpm to obtain the masterbatch;
[0088] The second aspect of the present invention provides an application of a preparation process of a high-performance polylactic acid meltblown fabric, which is used in the production of masks.
[0089] Comparative Example 1
[0090] The specific implementation method is the same as Example 3, except that the surface regulator is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), the weight portion is 0.6 parts, the mass ratio of poly(ethylene-co-glycidyl methacrylate) and poly(styrene)-block-poly(acrylic acid) is 0.5:0.2:0.1, the CAS number of polystyrene methyl methacrylate is 25034-86-0, purchased from West Asia Chemical Technology (Shandong) Co., Ltd., the CAS number of poly(ethylene-co-glycidyl methacrylate) is 26061-90-5, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., and the model of poly(styrene)-block-poly(acrylic acid) is 747009-500MG, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0091] Comparative Example 2
[0092] The specific implementation method is the same as that of Example 3, except that the heating temperature is 40° C.; the mixing time is 2 h; and the specific melt index is 70 g / 10 min, 190° C., and 2.16 kg.
[0093] Comparative Example 3
[0094] The specific implementation method is the same as that of Example 3, except that the heating temperature is 100° C.; the mixing and stirring time is 30 h;
[0095] Performance test: oil resistance, heat resistance
[0096] Oil resistance test: Soak the meltblown cloth in a mixture of rapeseed oil, peanut oil and soybean oil (mass ratio of 1:2:1) for 30 hours, soak the meltblown cloth in water for 15 minutes again, take it out and test the PM 2.5 filtration efficiency and air permeability again. The filtration efficiency is tested according to the standard "GB 19083-2010 Technical Requirements for Medical Protective Masks", and the air permeability is tested according to the standard "YY0469-2011" medical surgical masks.
[0097] Heat resistance test: The meltblown cloth was placed in an environment with a temperature of 90°C and a constant humidity of 95% for 170 hours. After being taken out, the PM 2.5 filtration efficiency and air permeability were tested again.
[0098]
Claims
1. A preparation process of high-performance polylactic acid meltblown cloth, characterized in that: The following steps are involved: (1) Add distilled water into a reaction kettle, raise the temperature, then add polylactic acid, carboxyl compound, reinforcing agent, compatibilizer, surface modifier, mix and stir to obtain mixture a, take a sample to detect the melt index of mixture a during stirring, stop the reaction when the specific melt index is reached, and discharge to obtain mixture b; (2) placing mixture b in a container, adding electret masterbatch and anti-hydrolysis masterbatch thereto, stirring and mixing, and obtaining mixture c; (3) adjusting the spraying temperature, spraying the mixture c, and then performing an electrostatic treatment to prepare a high-performance polylactic acid melt-blown cloth; The surface regulator is a compound of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid), and the mass ratio of polystyrene methyl methacrylate, poly(ethylene-co-glycidyl methacrylate), and poly(styrene)-block-poly(acrylic acid) is 0.5-1.2:0.7-0.9:0.3-0.5; The heating temperature is 65-85°C; The mixing and stirring time is 5-20 h; The specific melt index is 150-800 g / 10 min, 190° C., 2.16 kg.
2. The preparation process of a high-performance polylactic acid meltblown cloth according to claim 1, characterized in that: It is characterized in that The spraying temperature is 160-230°C.
3. The preparation process of a high-performance polylactic acid meltblown cloth according to claim 1, characterized in that: The carboxyl compound is a combination of one or more of tartaric acid, sodium benzoate, malic acid, adipic acid, citric acid, glycine, succinic acid, maleic acid, and acetic acid.
4. The preparation process of a high-performance polylactic acid meltblown cloth according to claim 1, characterized in that: The reinforcing agent is a combination of one or more of erucamide, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, polyhydroxybutyrate, acrylic acid-hydroxypropyl acrylate copolymer, polybutylene terephthalate-adipate, polymer polyol, and polycaprolactone.
5. According to the preparation process of a high-performance polylactic acid meltblown cloth according to claim 1, the compatibilizer is maleic anhydride grafted polyolefin.
6. An application of the preparation process of the high-performance polylactic acid meltblown fabric according to any one of claims 1 to 5, characterized in that: Used in the production of masks.
Citation Information
Patent Citations
Method for preparing electret melt-blown cloth material based on zeolite and polypropylene
CN112064134A
Preparation method of modified polypropylene melt-blown fabric subjected to electret treatment
CN112941723A
Polylactic acid hydrolysis-resisting fibre and preparation method thereof
CN101240464A
Melt-blown oil-absorbing wiping cloth
CN112680880A
Bio-based degradable polymer nanofiber and non-woven fabric
CN112813529A